Reference values of nonword repetition test for Brazilian Portuguese-speaking children - Simone Rocha de Vasconcellos Hage; Márcia Aparecida Grivol (University of São Paulo, 2009)
Evaluation of the phonological working memory (PWM) through repetition of nonwords can provide important information on the linguistic abilities of children, thus differentiating those with and without communication disorders. OBJECTIVE: The aim of this study was to obtain reference values in the Nonword Repetition Test (NWRT) in order to investigate the performance of children without language disorders concerning this type of memory. Material and METHODS: The study was conducted on 480 normal children of both genders aged 4 years to 8 years and 11 months, attending preschool and elementary school. The NWRT consisted of repeating 20 (children up to 4 years) or 40 (for children aged 5 years or more) invented words with 2 to 5 syllables. The results were subjected to descriptive statistical analysis. Comparison between ages and between the number of syllables in nonwords was performed by the Tukey's multiple-comparison test and one-way analysis of variance, at a significance value of p<0.05. RESULTS: There was statistically significant difference (p<0.05) in performance between children of different age groups, except between 7- and 8-year-olds. The analysis also showed statistically significant difference (p<0.05) in the number of syllables between the different age groups. CONCLUSIONS: The reference values obtained indicated an improvement in performance with the increase of age of children, indicating an improvement in the storage of verbal material in the PWM. The performance was worsened with the increase in the number of syllables in words, demonstrating that the greater the number of syllables, the greater is the difficulty in storing verbal material.